Brain and Critical Thinking in Education: A Bibliometric Review and Wordcloud Analysis - Afridha Sesrita; Asep Supena; Mohamad Syarif Sumatri; Gumgum Gumelar; Firmanul Catur Wibowo (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2024)
AbstractThis article uses data from the Scopus database for bibliometric review and wordcloud analysis visualization of publications related to Brain and Critical Thinking in Education (BCTE). The study highlights the importance of the brain in the learning process and critical thinking, as well as identifying research trends, key topics, and geographic distribution of authors over the decade 2013-2023. With a focus on English-language publications, the study reveals that